Wealth. Financial Liberalization, and the Demand for Money in Japan. (IMF Working Papers; Working Paper ;, 1989)
This paper presents estimates of a demand function for broad money in Japan. The function explains both secular trends in broad money during the 1970s and 1980s and the sharp decline in the income velocity of broad money during 1986-88. The inclusion of wealth and a measure of the return on holding broad money is essential to the specification of the money-demand function. Developments in these variables, as opposed to a behavioral shift brought about by the rapid pace of financial liberalization, explain the decline in money velocity during 1986-88.